Antioxidant property enhancement of sweet potato flour under simulated gastrointestinal pH - Chan, Kim Wei; Khong, Nicholas M. H.; Iqbal, Shahid; Imam, Mustapha Umar; Ismail, Maznah (MDPI AG, 2012)
Sweet potato is known to be rich in healthful antioxidants, but the stability of its antioxidant properties under gastrointestinal pH is very much unknown. Hence, this study aimed to evaluate the changes in antioxidant properties (total contents of phenolics and flavonoids as well as antioxidant activity) of sweet potato flour (SPF) under simulated gastrointestinal pH conditions. It was found that the yield of SPF crude phenolic extract increased from 0.29 to 3.22 g/100 g SPF upon subjection to gastrointestinal pH conditions (p < 0.05). Also elevated significantly were the total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity of SPF (p < 0.05). In summary, the antioxidant properties of SPF were enhanced under gastrointestinal pH conditions, suggesting that SPF might possess a considerable amount of bound phenolic and other antioxidative compounds. The antioxidant properties of SPF are largely influenced by pH and thus might be enhanced during the in vivo digestive process.